LENGTH-WEIGHT RELATIONSHIPS AND CONDITION FACTOR OF MALAJA FISH (Siganus canaliculatus) IN LUWU REGENCY WATERS - Nurilmi Achmad; Sunarti Sunarti; Andi Nur Apung Massiseng (Jurnal Perikanan Unram, 2024)
Malaja fish or baronang lingkis (Siganus canaliculatus) is a typical fish of the Luwu Regency community. This fish is favored in fishing activities by the local community because of its delicious taste. The main problem experienced by this fishery resource is that high fishing activities and increasing production volumes can result in stock decline. Therefore, it is necessary to study the growth patterns and condition factors of malaja fish in the waters of Luwu Regency as a basis for information for management activities. The purpose of this study was to determine length weight relationship and condition factor of malaja fish in Luwu Regency waters. Sampling was conducted from Mei to August 2024 with stratified random sampling method from catch landed at Karang-Karangan Village, Bua Sub-district, Luwu. The results showed that 168 fish captured consists of 88 males and 80 females. The length weight relationship was W = 0,000001L3,4556 for male and W = 0,00001L3,0421 for female. The results indicated that the length weight relationship was highly correlated (r > 90%). The relative condition factors of fish varied from 0,4475-2,6567.